Structural Properties of Syngenetic Ice-Rich Permafrost, as Revealed by Archaeological Investigation of the Yana Site Complex (Arctic East Siberia, Russia): Implications for Quaternary Science - Pitulko, Vladimir V.; Pavlova, Elena Y. (Frontiers in Earth Science, 2022)
Ice-rich syncryogenic (termed “Ice Complex”) deposits are common in northern East Siberia and constitute the most important feature of the Quaternary geology of the region. The Ice Complex formed throughout the Late Pleistocene and contains an archive of paleoenvironmental proxies such as Pleistocene faunal remains, but also comprises a record of human habitation spanning ~50,000 years, beginning with early MIS3. The development of syngenetic permafrost is an important variable in the formation of archaeological contexts in this depositional setting. Excavations of the Yana site complex in the lower Yana River area provide a unique opportunity to study archaeological finds preserved in Ice Complex deposits. Based on long-term field observations and dating results, we present important conclusions concerning the geology of the Yana sites. Taphonomic biases with potential to obscure the archaeological record are discussed. The thawing of frozen primary deposits has distorted depositional sequences, leading to the formation of secondary features and contexts, e.g., ice-wedge casts. Collapsed blocks of frozen sediment with undisturbed fragments of frozen layers containing artifacts and/or paleobiotic remains may become incorporated and refrozen into another depositional sequence and a source of misinterpretation and chronometric error. Furthermore, severe cryoturbation within the polygonal mounds warps the sediment in contact with the ice wedges; as a result, the contents of the sediment is uplifted with important consequences: (1) the hypsometric provenience of datable material is altered, creating chronometry problems; (2) in archaeology, there is an increased potential for misinterpretations with respect to dating, cultural classification, and human behavior; (3) transported material may form secondary concentrations at different hypsometric levels and thus bring further complications for its understanding; (4) in geology, the transportation of geochemical signatures may lead to erroneous interpretation of the geological potential of the area; (5) uplifted deposits contribute to increased Ice Complex thickness, which is thus not a direct function of sedimentation, but a combined result of sedimentation and re-distribution of the deposits within an existing polygon deposit. Thus, the analysis of Ice Complex deposits during archaeological excavations at the Yana site complex have wider implications for Quaternary science.